2020
DOI: 10.3390/molecules25214930
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of the Role of the Cannabinoid Compounds Δ9-Tetrahydrocannabinol (Δ9-THC) and Cannabidiol (CBD) and their Combination in Multiple Sclerosis Treatment

Abstract: Many people with MS (pwMS) use unregulated cannabis or cannabis products to treat the symptoms associated with the disease. In line with this, Sativex, a synthetic combination of cannabidiol (CBD) and Δ9-tetrahydrocannabinol (Δ9-THC) has been approved to treat symptoms of spasticity. In animals, CBD is effective in reducing the amounts of T-cell infiltrates in the spinal cord, suggesting CBD has anti-inflammatory properties. By doing this, CBD has shown to delay symptom onset in animal models of multiple scler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 83 publications
1
66
0
1
Order By: Relevance
“…CBD is the most commonly analysed phytocannabinoid after its psychotropic counterpart Δ 9 -THC [ 69 ]. The CBD-based therapeutic Epidoliex ® (Greenwich Biosciences, Carlsbad, CA, USA) has demonstrated significant merit in addressing TRE.…”
Section: Anticonvulsant Effects Of Phytocannabinoidsmentioning
confidence: 99%
“…CBD is the most commonly analysed phytocannabinoid after its psychotropic counterpart Δ 9 -THC [ 69 ]. The CBD-based therapeutic Epidoliex ® (Greenwich Biosciences, Carlsbad, CA, USA) has demonstrated significant merit in addressing TRE.…”
Section: Anticonvulsant Effects Of Phytocannabinoidsmentioning
confidence: 99%
“…Therefore, CBD in Sativex may intensify the beneficial effects of ∆ 9 -THC by reducing its psychoactive effect simultaneously. As described by Jones and Vlachou [76], the ability of CBD to inhibit the functional consequences of CB1 activation in the brain may be caused by the indirect enhancement of adenosine A1 receptors' activity through ENT inhibition. This process can clarify the lower risk of developing psychotic symptoms in patients who use preparations based on high ∆ 9 -THC and CBD ratios in comparison If conventional antispastic therapy is not efficient enough, then nabiximols, commercially known as Sativex (containing CBD and THC) were mainly recommended for the treatment of pain and spasticity in MS [72], but can also be applied in inflammatory disease therapy with demyelination and neuronal injury in the brain and spinal cord.…”
Section: Antioxidant Properties Of Cbdmentioning
confidence: 98%
“…Currently, it has not been proven that any known receptor site can be connected with CBD. Moreover, the molecular pharmacology of CBD has not been well defined yet [ 76 ]. Due to the high risk of side effects, the efficacy of treatments for MS is very limited.…”
Section: Recent Developments On the Molecular Mechanism Of Action Of Cbd For Multiple Sclerosis (Ms)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was first synthesized by Roger Adams ( Adams, 1942 ) and isolated by Mechoulam and Shvo in 1963 ( Mechoulam et al, 1963 ), from which a growing interest in its pharmacological actions began to emerge. The results from basic and clinical studies suggested that CBD may present beneficial effects for the management of neurological disorders such as epilepsy ( Carlini and Cunha, 1981 ; Devinsky et al, 2014 ; Devinsky et al, 2016 ), multiple sclerosis ( Kozela et al, 2011 ; Giacoppo et al, 2015 ; Jones and Vlachou, 2020 ), Parkinson’s ( Zuardi et al, 2009 ; Chagas et al, 2014 ) or Alzheimer’s diseases ( Martín-Moreno et al, 2011 ; Cheng et al, 2014 ). Moreover, there is a growing body of evidence suggesting that CBD improves cognition ( Osborne et al, 2016 ) and neurogenesis ( Liput et al, 2013 ; Schiavon et al, 2016 ), and presents antipsychotic ( Zuardi et al, 1991 ; Moreira and Guimarães, 2005 ; Long et al, 2006 ; Leweke et al, 2012 ; Leweke et al, 2016 ; Peres et al, 2016 ), anxiolytic ( Guimarães et al, 1990 ; Moreira et al, 2006 ; Resstel et al, 2006 ; Blessing et al, 2015 ) and antidepressant-like effects ( Zanelati et al, 2010 ; Linge et al, 2016 ; Sartim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%